Cardamine occulta Hornem. – a new alien small flowered bittercress (Cardamine L., Brassicaceae) of the Belarusian flora - Dzhus, Maxim A. (Experimental Biology and Biotechnology, 2019)
Brief revision of small flowered bittercresses (Cardamine L., Brassicaceae) in Belarusian flora is carried out. Distribution maps of all species from this group in Belarus (Cardamine parviflora L., C. hirsuta L., C. flexuosa With., C. impatiens L.) based from the herbarium material are presented. Alien East Asian weedy species C. occulta Hornem. (Brassicaceae) is mentioned for the flora of Turkey (Side village) and Belarus for the first time. The species was collected in Belarus in 2010 in Minsk city and on the territory of the Berezinsky biosphere reserve. Previously, C. occulta was often wrongly identified as C. hirsuta. The main diagnostic features of C. occulta and its differences from morphologically similar species of small flowered bittercresses are noted. Further expansion of C. occulta and C. hirsuta as a weeds with the container ornamental plants is very likely in future all over the territory of Belarus.
Keywords: Cardamine occulta; small flowered bittercresses; flora of Belarus; distribution; alien species